2015
DOI: 10.1364/boe.6.000347
|View full text |Cite
|
Sign up to set email alerts
|

Optical polarization tractography revealed significant fiber disarray in skeletal muscles of a mouse model for Duchenne muscular dystrophy

Abstract: Optical polarization tractography (OPT) was recently developed to visualize tissue fiber architecture with cellular-level resolution and accuracy. In this study, we explored the feasibility of using OPT to study muscle disease in the mdx4cv mouse model of Duchenne muscular dystrophy. The freshly dissected tibialis anterior muscles of mdx4cv and normal mice were imaged. A "fiber disarray index" (FDI) was developed to quantify the myofiber disorganization. In necrotic muscle regions of the mdx4cv mice, the FDI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Calcium deposits serve as a histological hallmark of DMD but not obviously of other myopathies, e.g., myotonic dystrophy type 1 [ 17 ]. Until now, analyses were performed either histologically or with gross anatomy imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT), or recently optical coherence tomography [ 18 21 ]. While histological sectioning offers highly detailed examination of single slices, it seems vastly time- and labor-consuming, not suitable for performing comprehensive analyses on the entire organs/organism.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium deposits serve as a histological hallmark of DMD but not obviously of other myopathies, e.g., myotonic dystrophy type 1 [ 17 ]. Until now, analyses were performed either histologically or with gross anatomy imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT), or recently optical coherence tomography [ 18 21 ]. While histological sectioning offers highly detailed examination of single slices, it seems vastly time- and labor-consuming, not suitable for performing comprehensive analyses on the entire organs/organism.…”
Section: Introductionmentioning
confidence: 99%
“…However, OPT can nondestructively image fiber orientation and birefringence at different depths from the tissue surface, which is not feasible in PLM. Recent studies have demonstrated that OPT can be potentially applied to image fiber structures in skeletal muscle, 31 heart muscle, 32 and blood vessels. 33 In this study, we showed that OPT can image collagen fiber orientation in the superficial layer of the articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest explanation is that the amount of ongoing necrosis of dystrophic muscles was much higher in the Bl10/ mdx , compared with D2/ mdx , mice. The new technology OPT (optical polarization tractography) allows to reconstruct organization of a whole fiber and may be useful to look deeper at all histological aspects, especially in mixed fast/slow muscles like the tibialis anterior [ 13, 14 ].…”
Section: Histological Measuresmentioning
confidence: 99%